How does communication influence the perceived performance of maintenance services in multi-storey public housing? - Yosof, Nor’Aini; Abdullah, Shardy; Mohd Najib, Nurul ‘Ulyani (International Journal of Strategic Property Management, 2014)
Currently, debates on the performance of maintenance services in multi-storey public housing have been matters of great concern. Previous studies have proven that a close relationship between the residents and the management team is vital to enhance the performance of maintenance services, but limited studies have been geared towards the influence of communication on the performance of maintenance services. This study aims to examine the influence of communication between the residents and the management team on the performance of the maintenance services. A survey was conducted with the residents of multi-storey public housing in Penang, Malaysia, who were selected using stratified random sampling. A descriptive analysis, Pearson product-moment correlation, and multiple regression analysis were used to analyse the data. The results show that there is a significant and positive relationship between effective communication and the residents’ perceived performance of maintenance services. Two communication attributes, “satisfaction with the feedback” and “accuracy of information”, are the determinants for the performance of maintenance services. First Publish Online: 8 Dec 2014